Model Hubungan antara Citra Merek, Kualitas Layanan, dan Kepuasan Pelanggan pada PT Sejahtera Surya Intramedika - Noval Maula Ramadhan; Mariana Puspa Dewi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to empirically examine and analyze the influence of Brand Image and Service Quality on Customer Satisfaction at PT Sejahtera Surya Intramedika within the context of a Business-to-Business (B2B) pharmaceutical distributor. This research is crucial given the intensifying competition in the healthcare industry and the mandatory compliance with strict drug distribution regulations. Employing a quantitative causality approach, this study collected data from 101 customer respondents (pharmacies) determined through a multistage sampling technique combining cluster and purposive sampling based on operational area criteria including Blitar City, Kediri, Tulungagung, and Pare, as well as a specific minimum transaction volume. Data analysis was conducted using multiple linear regression methods assisted by SPSS software to test the hypotheses. Statistical test results indicate that partially, Brand Image has a positive and significant effect on customer satisfaction with a regression coefficient of 0.347. Service Quality was also proven to have a positive and significant effect, and was identified as the most dominant variable with a coefficient of 0.620. Simultaneously, both variables contributed 69.6% influence to the variation in customer satisfaction, as validated by the calculated F-value of 112.166. This study concludes that the synergy between a professional brand image and responsive service quality is a fundamental key to company success. Practical implications suggest that management should prioritize investment in logistics reliability and personnel competence to strengthen strategic partnerships and ensure sustainable customer satisfaction amidst the dynamics of the competitive pharmaceutical market.